Dos versiones rivales sobre la tolerancia: La crítica de Michael Sandel a John Rawls - Correa Casanova, Mauricio (Veritas, 2006)
In the presente article the author analyzes two rival versions of tolerance sustained in moral philosophy and contemporary politics. It starts by exposing Michael Sandel’s thinking over two models of moral argument that are at the base of political debate. Then, he exposes the two rival models of tolerance, that is, the «no-judgmental tolerance» and the «judgemental tolerance». As an illustration of the impossibility of «non-judgemental tolerance» the situation on the debate on abortion in the American constitutional argument is developed, with special emphasis in rawls’s argument based on public reason. Finally, the advantages and inadequacies that, in the author's opinion, come off of both versions of tolerance are shown.